2011
DOI: 10.1245/s10434-011-2054-z
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Analysis of Human Equilibrative Nucleoside Transporter-1 (hENT1) Predicts Survival in Resected Pancreatic Cancer Patients Treated with Adjuvant Gemcitabine Monotherapy

Abstract: A high expression of hENT1 in pancreatic cancer was found to be significantly associated with a longer survival in patients who received adjuvant gemcitabine monotherapy after curative resection, and hENT1 immunohistochemistry may well serve as a significant prognostic factor for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 10 publications
3
51
1
2
Order By: Relevance
“…Ultimately, we identified 5 patients with high hENT1 staining and 7 patients with low hENT1 staining (Supplemental Figure 8). Although the semiquantitative nature of hENT1 intensity scoring limits this methodology, the final classification was similar to previous work (15,17). In this manner, we found that hENT1 score significantly correlated with normalized gemcitabine incorporation ( Figure 3A).…”
Section: Figuresupporting
confidence: 84%
“…Ultimately, we identified 5 patients with high hENT1 staining and 7 patients with low hENT1 staining (Supplemental Figure 8). Although the semiquantitative nature of hENT1 intensity scoring limits this methodology, the final classification was similar to previous work (15,17). In this manner, we found that hENT1 score significantly correlated with normalized gemcitabine incorporation ( Figure 3A).…”
Section: Figuresupporting
confidence: 84%
“…117,168 Therefore, reduced expression of nucleoside transporters on tumor cells causes tumor cell resistance to gemcitabine. 123,169 For example, it was reported that high hENT1 expression in resected specimen of patients with PDAC who received postoperative gemcitabine therapy is correlated with increased overall survival, [170][171][172][173] whereas low hENT1 expression was linked to gemcitabine resistance and shorter overall survival. 109,123,169 In addition, low levels of hENT1 expression were also detected in tumors in gallbladder adenocarcinoma patients who respond poorly to gemcitabine.…”
Section: Increasing Cellular Uptake Of Gemcitabinementioning
confidence: 99%
“…Of these articles, 23 were excluded after a review of their titles and key words; then, abstracts and full texts were reviewed, and another 23 articles were excluded. Eleven clinical studies met our inclusion criteria for this meta-analysis (Spratlin et al, 2004;Giovannetti et al, 2006;Farrell et al, 2009;Marechal et al, 2009Marechal et al, , 2012Fujita et al, 2010;Kim et al, 2011a;Kondo et al, 2012;Morinaga et al, 2012;Murata et al, 2012;Nakagawa et al, 2013). The flow chart of the study selection process is shown in Figure 1.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…In vitro studies also showed that high hENT1 gene expression was significantly associated with increased chemosensitivity to gemcitabine (Mori et al, 2007;Michalski et al, 2008). Several previous studies have indicated that high hENT1 protein/mRNA expression was associated with increased overall survival (OS) and disease-free survival (DFS) (Farrell et al, 2009;Marechal et al, 2012;Morinaga et al, 2012). However, there are also some contradictory data in the literature concerning the prognostic value of hENT1 in predicting gemcitabine chemosensitivity for pancreatic cancer patients (Fujita et al, 2010).…”
Section: Introductionmentioning
confidence: 99%